Poeta Classicus: Was Horace in the Fleet during the Battle of Actium? - Egorova, Sofia (Hyperboreus, 2017)
The author strives to disprove the common assumption that Horace was present in the ﬂeet during the Battle of Actium, and that he wrote the 9th Epode aboard. In fact, the poet never explicitly states this. Therefore the ﬁrst section of the article compares the 9th Epode with descriptions of two events that Horace claims to have experienced himself: the battle of Philippi and the shipwreck by Capo Palinuro. Also the use of spatial reference points is considered, which would suggest that the narrator was present at the battle. Meanwhile the at huc (1. 17) is a medieval correction of a clumsy ad hunc, and the adverb sinistrorsum (1. 20) means usually ‘to the left in the course of travel’ and does not necessarily imply the narrator’s point of reference. Finally, the author compares the passage under scrutiny with another of the poet’s works: Carm 2. 6. and Epist. 1. 20. In the former Horace describes his lengthy experience of military service, exaggerating visibly, while his tone in Epist 1. 20. 23 is rather ironic and does not imply any autobiographical details. Furthermore, this author believes that the phrase belli domique refers to the adjective primis, rather than placuisse.